(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
The present research, with a qualitative approach, aimed to identify the conceptions of 27 third-year Elementary School students from the Public Network of São Mateus/ES regarding Environmental Education, specifically on the identification, separation, and recycling of materials, the separation of organic waste and its reuse in composting, and the recycling of used paper. The topics were developed in three workshops, starting with the application of Diagnostic Questionnaires containing open and closed questions. At the end of the project, an Evaluative Questionnaire was applied. The results showed that the students understood the need for environmental preservation and the impacts caused by its absence. However, few students knew how the processes of selective collection, recycling, and reuse of organic waste could be carried out in practice. Through the workshops, it was possible to notice the appropriation of the developed contents, as well as their understanding of the need to adopt environmentally responsible habits through simple actions that can be performed at home to promote environmental preservation.